2009
DOI: 10.1007/s10495-009-0348-4
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase-3β regulates etoposide-induced apoptosis via Bcl-2 mediated caspase-3 activation in C3H10T1/2 cells

Abstract: Glycogen synthase kinase-3beta (GSK3beta) controls the survival of osteoblasts during bone development through Wnt canonical signaling. GSK3beta is a key factor for osteoblastogenesis, but relatively less is known regarding its role in osteoblast apoptosis. Genotoxic stress induced by etoposide promoted apoptotic signaling by GSK3beta activation in C3H10T1/2 cells, a mouse mesenchymal cell line. Etoposide led to the time-dependent activation of GSK3beta and caspase-3, which resulted in PARP cleavage. LiCl (a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 20 publications
3
10
0
Order By: Relevance
“…Consistent with previous results in INS-1E ␤-cells (14), we found that cytokine treatment increased cleaved caspase3 activity in the MIN6 ␤-cells, whereas treatment with EX4 decreased cytokine-induced caspase3 levels. However, in addition to proliferation, several downstream mediators of cWnt signaling has been found to regulate apoptosis in a variety of cell types, including ␤-cells (35)(36)(37)(38)(39)(40)(41)(42). The present study shows, for the first time, that Rspo1 inhibits cytokine-induced apoptosis in the MIN6 ␤-cells.…”
Section: Discussionsupporting
confidence: 50%
“…Consistent with previous results in INS-1E ␤-cells (14), we found that cytokine treatment increased cleaved caspase3 activity in the MIN6 ␤-cells, whereas treatment with EX4 decreased cytokine-induced caspase3 levels. However, in addition to proliferation, several downstream mediators of cWnt signaling has been found to regulate apoptosis in a variety of cell types, including ␤-cells (35)(36)(37)(38)(39)(40)(41)(42). The present study shows, for the first time, that Rspo1 inhibits cytokine-induced apoptosis in the MIN6 ␤-cells.…”
Section: Discussionsupporting
confidence: 50%
“…Under these conditions, the PI3K/Akt pathway downstream of Jak2 is downregulated, thus reducing the inhibitory phosphorylation of GSK3β. According to previous reports, GSK3β is also activated by etoposide or ceramide, which may be mediated indirectly through PP2A activation [14], [22], [23]. In accordance with this, etoposide or doxorubicin reduced the inhibitory phosphorylation of GSK3β, which was inhibited by the PP2A inhibitor okadaic acid (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…5A), thus suggesting that molecular mechanisms other than that regulating cell cycle progression may also play an important role in activation of apoptotic signaling downstream of GSK3β. In this regard, GSK3β has been implicated in direct or indirect activation of Bax, caspase-2, and caspase-3 leading to apoptosis [14], [23], [24]. These possibilities as well as the mechanisms involved in GSK3β activation under DNA damage stress need to be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are two GSK3 isoforms in mammalians that are encoded by distinct genes: GSK3a and GSK3b. GSK3b has differential roles in the regulation of transcriptional activation and apoptosis (Park et al, 2009;Yun et al, 2009). GSK3b is recognized as much potential tumor suppressor as GSK3 phosphorylated pro-oncogenic molecules such as c-Jun, c-Myc, CREB, CCND1, and b-catenin.…”
Section: Discussionmentioning
confidence: 99%